Penggunaan Persenjataan Modern Dalam Konflik Bersenjata Ditinjau Dari Prinsip Hukum Humaniter Dan Hukum Islam - Alamsyah, Yazid Akbar; ibnu akbar, Rafi Ilyasa (Sanskara Hukum dan HAM, 2024)
This study combines the perspectives of international humanitarian law and Islamic law to analyze the use of modern weapons in armed conflict. In an effort to protect victims of war, including civilian populations, international humanitarian law is applied based on the principles of humanity, proportionality and distinction. On the other hand, Islamic law, which is derived from the teachings of the Quran and Hadith, emphasizes the importance of protecting people who are not involved in combat as well as protecting the environment during war. However, advances in military technology, such as the use of drones and long-range missiles, have created new challenges in the application of these two legal systems. Unavoidable civilian casualties are often a consequence of the use of such technology, raising questions about the relevance of religious law and international law in the modern context. This study utilizes a normative juridical approach, which considers legal principles and historical background. The aim is to evaluate the impact of the use of modern weapons in armed conflicts and identify possible violations.